Face adaptation effects show strong and long-lasting transfer from lab to more ecological contexts - Carbon, Claus-Christian; Ditye, Thomas (Frontiers in Psychology, 2012)
A review on recent experiments on figural face aftereffects reveals that adaptation effects in famous faces can be quite sustainable, lasting for hours up to days. Such adaptations also seem to be highly reliable regarding test-retest designs as well as regarding the generalizability of adaptation across different adaptation routines and adaptations towards different kinds of facial properties. However, in adaptation studies conducted so far, the adaptation as well as the subsequent test phase was carried out in typical laboratory environments. Under these circumstances, it cannot be ruled out that the observed effects are, in fact, episodic learn-test compatibility effects or representational effects. To test adaptation effects for ecological validity we used an adaptation paradigm including environmental, situational and social properties that differed significantly between adaptation and test phase (ecological condition). With matched samples (n1=n2=54) we found neither main effects of experimental setting compatibility nor any interaction with effects of stimulus compatibility operationalized by varying stimulus similarity between adaptation and test phase: same picture (condition picture), different pictures of the same person (condition identity) or different persons (condition novel). This indicates that these adaptation effects are not artificial or merely lab-biased effects. They rather seem to document representational adaptations and tuning mechanisms that integrate new visual input in a very fast, reliable and sustainable way.